1999
DOI: 10.1002/(sici)1096-8644(199906)109:2<147::aid-ajpa1>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins of the mtDNA 9‐bp deletion in populations of South India

Abstract: The origins and genetic affinities of the more than 500 tribal populations living in South Asia are widely disputed. This may reflect differential contributions that continental populations have made to tribal groups in South Asia. We assayed for the presence of the intergenic COII/tRNALys 9-bp deletion in human mtDNA in 646 individuals from 12 caste and 14 tribal populations of South India and compared them to individuals from Africa, Europe, and Asia. The 9-bp deletion is observed in four South Indian tribal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Earlier studies (Barnabas et al 2000;Clark et al 2000;Watkins et al 1999) have also indicated that this 9-bp deletion is extremely infrequent in India. As observed by us earlier (Roychoudhury et al 2000), there is extensive sharing of haplotypes across ethnic groups; one haplotype (00111101010) was modal across all the populations.…”
Section: Figmentioning
confidence: 82%
“…Earlier studies (Barnabas et al 2000;Clark et al 2000;Watkins et al 1999) have also indicated that this 9-bp deletion is extremely infrequent in India. As observed by us earlier (Roychoudhury et al 2000), there is extensive sharing of haplotypes across ethnic groups; one haplotype (00111101010) was modal across all the populations.…”
Section: Figmentioning
confidence: 82%
“…2). Previously published mtDNA data that was considered here included 78 Africans (32 with the deletion), 336 Amerindians (63 with the deletion), 118 Australian aboriginals (4 with the deletion), 29 Taiwan aboriginals (12 with the deletion), 74 Pacific Islanders with the 9-bp deletion (27 Indonesians, 23 coastal Papua New Guinea, and 24 Samoan), 99 Indians (6 Nicobarese and 22 South Indians with the deletion), 6 Chinese, and 4 Cambodians with the deletion (Ward et al 1991(Ward et al , 1993Vigilant et al 1991;Santos et al 1994;Kolman et al 1995;Redd et al 1995;Mountain et al 1995;Betty et al 1996;van Holst Pellekaan et al 1998;Melton et al 1998;Krings et al 1999;Watkins et al 1999). Except for the 28 Taiwan aboriginal (Melton et al 1998) and 71 Indians (Mountain et al 1995) sequences from Dr. T. Melton and Dr. J. L. Mountain respectively, all other sequences were from the mtDNA database (http://www.eva.mpg.de/hvrbase; Handt et al 1998) or GenBank.…”
Section: Data Analysesmentioning
confidence: 99%
“…The deletion motif occurs at varying frequencies in Asian, Oceanic, and Amerindian populations (Ballinger et al 1992;Harihara et al 1992;Passarino et al 1993;Sykes et al 1995;Betty et al 1996;Melton et al 1995Melton et al , 1998Lum et al 1998;Merriwether et al 1999;Watkins et al 1999;Shurr et al 1990;Ward et al 1991;Shields et al 1992;Kolman et al 1995). Additional reports have demonstrated the presence of the 9-bp deletion in African (Soodyall et al 1996;Watkins et al 1999) and European (Torroni et al 1995;Thomas et al 1998) populations. The coalescent times of the 9-bp deletion haplotypes are estimated to be 50,000-70,000 years before present (YBP; Redd et al 1995;Soodyall et al 1996; Thomas et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations